How the Mamluk Sultan Addressed the Golden Horde’s Khan. The Form of Letters and Rules for Their Compilation - Marie Favereau (Золотоордынское обозрение)
Research objectives: To study some questions of form and protocol by which the Mamluks were guided in their “written relations” with the Chinggisids of the Golden Horde. To determine the degree of mutual influence between Turkic, Mongol and Arabic epistolary practices of this period. Research materials: Examples from the clerical manuals of the three major writers of the Mamluk sultanate: Ibn Fadl Allah al-Umari (al-Ta‘rīf fī al-muṣṭalaḥ al-šarīf) (d. 749/1349), Ibn Nazir al-Jaysh (al-Taṯqīf fī al-taʿrīf) (d. 786/1384), and al-Qalqashandi (Ṣubḥ al-aʿšā fī ṣināʿat al-inšā’) (d. 821/1418). Research results and novelty: The author analyzed in detail the above sources, confirming the interaction between the two diwans al-insha’ as well as the circulation of Islamic chancellery knowledge and techniques between Egypt and Central Asia, starting from the second half of the 13th century and up to the first half of the 15th century. As a result, it has been revealed that administrative institutions functioned steadily despite the periodic discontinuity and chaos of dynastic inheritance. The statements that we distinguish through these epistolary exchanges also possess a certain continuity; the goal of most of these letters was to justify or ask a question about prolonged silences, the shortage of embassies, and the long absence of an exchange between the two states. Consequently, the diplomatic practices of the Mamluks and Golden Horde fit into the long favorable period of the general evolution of clerical regulations.